(untitled) (Revista Electrónica REDINE, 2019)
The present qualitative research, has as intentions to unveil, interpret, understand and generate, a body of knowledge inherent in the vision of teachers of the Master’s Program in Educational Research of the UPEL-IPB on the multimethod approach as a research method. Being inserted in the Research Line: Qualitative Research Network in Education. The research was approached under the shelter of the socio-constructionist paradigm, supporting me methodologically in hermeneutical phenomenology with techniques typical of symbolic interactionism, which detected the collection and analysis of the findings; Ontologically it is Relativistic, since there are multiple versions of reality, as well as epistemologically transactional-dialogic-subjective sea, since knowledge was sustained by the interpretation obtained by social actors; for the collection of the information, the participant observation and the in-depth interview were selected, selecting the key informants through an intentional sampling, which gave birth to the investigation; All this served to demonstrate the importance of understanding and using new approaches for the elaboration of degree work in the masters of educational research.